DETERMINATION OF FRACTURE PATTERNS OF A BRAND OF STAINLESS STEEL K FILES; AN IN VITRO STUDY - Saeedullah, Maryam; Husain, Syed Wilayat (Pakistan Oral & Dental Journal, 2018)
Objective of the study was to qualitatively determine and compare the fracture patterns of hand held stainless steel K files (Mani, Inc. Japan), acquired from Pakistan and United Kingdom. This study was conducted at the Institute of Space Technology, over a period of one month.A total of 40 stainless-steel K files (Mani, Inc. Japan) of identical size (ISO#25) were collected and divided into two groups, such that Group A consisted of 20 K files acquired from the Rawalpindi/ Islamabad region in Pakistan while Group B consisted of 20 K files that were purchased from London, UK. The files were fractured one by one, 3mm from the tip. The fractured surfaces were then observed under scanning electron microscope to determine their fracture patterns.Evaluation of the fractured surfaces revealed decreased ductility in Group A in comparison with Group B.Stainless steel endodontic files available commercially in Pakistan need evaluation of their fracture behavior for patient safety and benefit.
Keywords: Stainless steel endodontic K files; fractography; ductility; brittleness